In-game photography: jogando com poiéticas na pós-fotografia - Leonardo Ferreira (2023)
Having our poetics as a place of thought in an art-based research, we approach the in-game photography (IGP), the mechanically mediated creation of fixed images without the sensitizing of media through the action of light based on engaging (sometimes more, sometimes less subversively) with digital games. To understand its potential in a contemporary hybrid arts perspective, we articulate texts about IGP, such as those by Cindy Poremba, which explore the relationship between such practice/logic and photography, as well as writings about the status of still images in the face of the advent of the digital, in particular investigating the term post-photography according to Ronaldo Entler and Joan Fontcuberta among others. Problematizing the relationship between technologies and the social, starting from discussions such as those of Bruno Latour, we address the imbrication of materialities and conceptualizations with creation processes of artworks in a rhizomatic ontology. Having the phenomenological issue of computer data as a foundation, we articulate the problematizations to specific points of our aesthetics, such as the influence of the concept of videographic device on Philippe Dubois and its reinterpretation on Cesar Migliorin; the idea of variability in Lev Manovich; and the physical/virtual reality relationship in André Lemos. At the end, we suggest that in-game photography does not need to be limited to the two-dimensional plane of the image, relating to different issues, privileging, in our case, a metalinguistic character of the IGP. Furthermore, that the dispute over the concept of post-photography matters more for the knowledge that emerges from the debate than for the adoption or not of the term in a context of transformations of photography over a history of almost 200 years, with the IGP being conected to it by, among other things, sharing the same regime of (making) visible.